Germinação de sete espécies do cerrado paulista com potencial paisagístico: Germination of seven native cerrado species from São Paulo state with landscape potential - Bincoleto, Victor Augusto; Weiser, Veridiana de Lara; Enokibara, Marta (Technical and Scientific Journal Green Cities, 2025)
Objective – The study evaluated the germination of seven native cerrado species from São Paulo state with landscaping potential: Tilesia baccata, Achyrocline satureioides, Mimosa debilis, Vernonanthura polyanthes, Andropogon fastigiatus, Andropogon leucostachyus, and Loudetiopsis chrysothrix. The research aimed to provide parameters that enable the introduction of these species into landscaping, with the aim of enhancing the native flora of the São Paulo cerrado.Methodology – Indirect sowing of the selected species was carried out in cells, with monitoring conducted over ten weeks, during which the germination rate was analyzed.Originality/Relevance – There is little literature available on the germination of the species under study, and variations in germination rates were identified in the data collected.Results – The species Andropogon fastigiatus, Andropogon leucostachyus, Loudetiopsis chrysothrix, Mimosa debilis, and Tilesia baccata showed low germination and seedling emergence rates during the analyzed period. On the other hand, Achyrocline satureioides and Vernonanthura polyanthes presented relevant germination/seedling emergence rates.Theoretical/Methodological Contributions – The research provides experimental data regarding the feasibility of using cerrado species in landscaping, considering germination criteria.Social and Environmental Contributions – The study highlights the importance of Cerrado conservation and the relevant role that gardens can play as a form of ex situ conservation.
Keywords: Native species; Seed germination; Seedling growth